L’ordre social et son gouvernement en perspective coloniale. Pour une histoire trans-territoriale de l’Espagne contemporaine - François Godicheau; Alina Castellanos Rubio (Amnis)
This article considers a joint, and not comparative, history between Spain's overseas possessions and its European space for the 'second empire' (19th-20th centuries). It is joint because all the territories of the Catholic monarchy were confronted with common problems at that time, to which different solutions were of course found, but which does not prevent a joint approach. The study of social control, the government of the social order, is a privileged field of this. By observing both the logics of transformation of the institutions inherited from the Old Regime common to all these territories, and the particularities that make Cuba an exceptional terrain for economic and political experimentation, this article intends to show that the understanding of the phenomena of the government of the social order, like many others, must undoubtedly take into account the trans-territorial and global dimension of contemporary Spain.